DYNAMICS AND RELIABILITY OF A MAN-MACHINE SYSTEM - Tran, Van Dac (Periodica Polytechnica Mechanical Engineering, 1987)
This study deals with the dynamics and reliability of a man-machine system with the technical part containing a hydraulic servomechanism. A new method has led to some interesting results of use for both analysis and synthesis of such system. Furthermore, with a convenient modification these results may be generelized for studying other structural systems. Investigation of the system reliability is based on concept of multistate system analysis.